Invasive species in the soil seed bank of two limestone hills in Bogor, West Java, Indonesia - Winda Utami Putri; Ibnul Qayim; Abdul Qadir (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Putri WU, Qayim I, Qadir A. 2021. Invasive species in the soil seed bank of two limestone hills in Bogor, West Java, Indonesia. Biodiversitas 22: 4019-4027. Study on the impact of invasive species on plant communities has been conducted mainly on the aboveground vegetation. The impact on the soil seed bank has received less attention mostly due to practical difficulties in conducting seed bank assessment. Evaluation of seed bank composition is useful in detecting invasive plant species that may have been present as buried seeds. Information on the vegetation composition in Nyungcung and Kapur hills both under and aboveground is available, but specific information on invasive species has not been discussed yet. This paper describes and analyzes the structure (composition and density) of invasive species in the soil seed bank. Eighty soil samples were taken from the study sites. The soil seed banks were analyzed using seedling emergence and seed extraction methods. 2602 and 1280 seedlings emerged from soil seed bank of Nyungcung and Kapur hills, respectively. From that number, approximately 48.96% and 68.51% of the seedlings are invasive species in the soil seed bank of Nyungcung and Kapur hills. The invasive species were dominants in the soil seed bank of the two sites. Cecropia peltata and Clidemia hirta were the most abundant invasive species in the Kapur and Nyungcung hills seed bank, respectively. Species richness and seedling density were higher in Nyungcung hills than Kapur hills, which were invaded for a relatively longer period.